Deadbeat control for a single-inductor multiple-input multiple-output dc-dc converter - Wang, Benfei (2020)
This paper presents a deadbeat-based method for the single-inductor multiple-input multiple-output (SI-MIMO) dc-dc converter. By solving the cross regulation problem of the SI-MIMO dc-dc converter, the proposed method is capable of achieving the input current regulation (ICR) and the output voltage regulation (OVR) simultaneously. Moreover, the output current observers are adopted to replace the output current sensors, which are required by the conventional model based methods for dc-dc converters. The proposed control approaches including ICR and OVR are discussed in detail. To verify the effectiveness of the proposed deadbeat-based method, simulation runs and experiments are conducted on the single-inductor dual-input dual-output buck converter simulation platform and hardware prototype, respectively. The simulation and experimental results are analyzed in detail, and the comparison with the previous works is conducted.